How Perceived Convenience, Usefulness, and Satisfaction Influence QRIS Payment Reuse Behavior in UMKM Context? - Abdul Rauf; Arvina Damayanti; Eka Hendra Priyatana; Maulana Yusuf (IECON: International Economics and Business Conference, 2025)
This study addresses the urgent need to understand factors influencing QRIS payment reuse among MSME customers in Indonesia's digital economy. The research aims to examine how perceived convenience, perceived usefulness, and satisfaction affect reuse intentions through a comprehensive theoretical framework. Using quantitative methodology with questionnaire data from 96 MSME customers at Tangerang City Mall, collected via accidental sampling and analyzed through PLS-SEM with SmartPLS software, this study reveals significant relationships between perceived convenience and satisfaction, perceived usefulness and satisfaction, and satisfaction and reuse interest. Novel findings demonstrate that while direct effects of perceived factors on reuse interest are insignificant, both perceived convenience and usefulness significantly influence satisfaction, which subsequently drives reuse intentions. This research contributes to payment technology adoption literature by validating mediation effects in emerging market contexts. However, limitations include the single-location sampling approach and cross-sectional design, suggesting future research should employ multi-location studies and longitudinal designs to enhance generalizability and capture dynamic behavioral patterns in digital payment adoption.